C. Aitmatov: world philosophy in the national literature (Herald of Journalism, 2020)
The article is devoted ideological and philosophical views of the writ- er, thinker, journalist, social activist Chingiz Aitmatov. Particular emphasis is placed on the moral and philosophical issues of works, the epic mindset of the author, the relevant national picture of the world. Written by the ex- ample of the life and work of the writer examines his humanistic ideals and philosophical problems of human life on Earth, is considering rethinking of ancient legends, folklore, based on the creation of sources of copyright myths, which have the primary meaning, as well as analyzes the construc- tion of the multi-layered storytelling, leading to a multi-level composition of the text.
Keywords: national literature, philosophical context, image, story, philosophical and journalistic prose, the author’s style.